KAJIAN KUALITAS AIR SUNGAI NIMANGA SEBAGAI SUMBER AIR IRIGASI PERSAWAHAN DESA PASLATEN KECAMATAN TATAPAAN KABUPATEN MINAHASA SELATAN - Vira Dewi Sumual; J.V Bobby Polii; Tommy B. Ogie (Universitas Sam Ratulangi, 2019)
ABSTRACT This research aims to determine the water quality of Nimanga River in Tatapaan Sub district of South Minahasa Regency which became the source of paddy field irrigation in Paslaten village. This research was done for two months, namely in March to April, the location of water sampling is located at the five Points of Nimanga River (first point), irrigation (second point), Paddy Field A (Third point), field tile B (point Fourth), the end channel of the Paddy Field (fifth point), was done twice as much as the analysis in the BARISTAN laboratory. Based on the results of the analysis can indicate that the concentration of DHL on the first sample at the first point (0.317 DS/M), the second point (0, 330DS/m), the third point (0.328 DS/M), the point of the four (0.330 DS/M), the point of Kelim (0.333 DS/M), in good quality. The concentration of TDS in the first sample at the first point (260 mg/l), the second point (260 mg/l), the third point (289 mg/L), the fourth point (280 mg/L), the fifth point (221 mg/l), in good quality. The pH concentration in the first sample at the first point (7.22), the second point (7.89), the third Point (7.92), the fourth point (7.92), the fifth point (7.92), in good quality. Nitrate concentrations in the first sample at the first point (0.167 mg/l), the second point (0.678 mg/l), the third point (0, 652 mg/l), the fourth point (0, 339 mg/L), the fifth point (0, 370 mg/l), in good category. Concentrations of Clorida in the first sample at the first point (25.46 mg/l), the second point (27.34 mg/l), the third point (25.46 mg/l), the fourth point (29.23 mg/L), the fifth point (46.20 mg/l), in good quality. Then for the concentration of DHL on the second sample at the first point (0.330 DS/M), the second point (0.341 DS/M), the second point (0.338 DS/M), the fourth point (0.336 DS/M), the fifth point (0.334 DS/M), in good quality. The concentration of TDS in the second sample at the first point (308 mg/L), the second point (292 mg/l), the third point (307 mg/L), the fourth point (289 mg/L), the fifth point (271 mg/l), in good quality. The concentration of pH in the second sample at the first point (6.95), the second point (7.17), the third Point (7.19), the fourth point (7.11), the fifth point (6.94), in good quality. The concentration of nitrate in the second sample at the first point (0.60 mg/l), the second point (0.73 mg/l), the third point (0, 62 mg/L), the fourth point (0.40 mg/L), the fifth point (0.50 mg/l), in good condition. Concentrations of Clorida in the second sample at the first point (22 mg/L), the second point (20 mg/l), the third point (22 mg/L), the fourth point (21 mg/L), the fifth point (22 mg/l), in good quality. The results of the ansalisis which can show in either category or qualified in accordance with the value of standard quality water irrigation of Ayers and Westcot, 1985. Keywords: water quality, irrigation